2005
DOI: 10.1186/1471-2261-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for hypertension in the United States

Abstract: Background: Despite heavy recent emphasis on blood pressure (BP) control, many patients fail to meet widely accepted goals. While access and adherence to therapy certainly play a role, another potential explanation is poor quality of essential care processes (QC). Yet little is known about the relationship between QC and BP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
6
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 22 publications
4
44
6
6
Order By: Relevance
“…Although our analyses do not directly demonstrate that therapy modifications led to better control, their validity is indirectly supported by the several randomized, controlled trials that have demonstrated the efficacy of these pharmacotherapeutic interventions (1)(2)(3)(4)(5). Several previous studies have also shown that clinical inertia was associated with poor risk factor control (12,39) and intensification of therapy with better control (17,(39)(40)(41). A final validation would examine whether higher rates of treatment intensification or "appropriate care" are associated with better levels of control across populations or over time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although our analyses do not directly demonstrate that therapy modifications led to better control, their validity is indirectly supported by the several randomized, controlled trials that have demonstrated the efficacy of these pharmacotherapeutic interventions (1)(2)(3)(4)(5). Several previous studies have also shown that clinical inertia was associated with poor risk factor control (12,39) and intensification of therapy with better control (17,(39)(40)(41). A final validation would examine whether higher rates of treatment intensification or "appropriate care" are associated with better levels of control across populations or over time.…”
Section: Discussionmentioning
confidence: 97%
“…Such measures have been proposed to have several advantages over simpler process measures, such as rates of risk factor testing, and also over levels of control. Intensification of therapy, but not higher testing rates for risk factors (7,19), has been shown to lead to better control (17,(39)(40)(41). For example, a study in 30 U.S. academic medical centers found a very high proportion of testing rates (88% to 97%) for cardiovascular risk factors in patients with diabetes, but a low proportion of patients in control (33% to 46%) and a low rate of therapy modifications in those with elevated risk factor levels (14% to 46%) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by several studies that have separately investigated concordant and discordant patient comorbidities. Some have reported the positive impact of separate concordant comorbidities on the management of cardiovascular risk factors, 23,24 whereas others have found negative impacts of individual discordant comorbidities on management of these risk factors. [25][26][27] We believe this is the first study to examine the concurrent, separate, and linear contributions of concordant and discordant comorbidities on management of a single cardiovascular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Asch et al 24 have recently described the correlates of optimal care of patients with hypertension using explicit indicators of the care process. They observed that the following categories of hypertensive patients were more likely to receive optimal care: those Ͼ50 years of age; patients with diabetes, coronary artery disease, or hyperlipidemia; and nonsmokers.…”
Section: Quality Of Hypertension Care: Impact Of Select Patient-relatmentioning
confidence: 99%